(untitled) (Journal of the College of Basic Education, 2022)
The burial rites of monks occupy an important part in the Christian faith, as the monks are usually buried inside the tafoos of their monasteries, so they did not follow new and different ways in burial, as the burial rituals were the same and their ceremonies were similar, but later those ceremonies differed according to the value of the deceased monk